2005
DOI: 10.1126/science.1106148
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Regulation of Akt/PKB by the Rictor-mTOR Complex

Abstract: Deregulation of Akt/protein kinase B (PKB) is implicated in the pathogenesis of cancer and diabetes. Akt/PKB activation requires the phosphorylation of Thr308 in the activation loop by the phosphoinositide-dependent kinase 1 (PDK1) and Ser473 within the carboxyl-terminal hydrophobic motif by an unknown kinase. We show that in Drosophila and human cells the target of rapamycin (TOR) kinase and its associated protein rictor are necessary for Ser473 phosphorylation and that a reduction in rictor or mammalian TOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

197
5,238
21
53

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,836 publications
(5,509 citation statements)
references
References 28 publications
197
5,238
21
53
Order By: Relevance
“…Mammalian target of rapamycin (mTOR) phosphorylates AKT on S473, and was present at comparable levels in platelets from normal and affected horses at these time points. This also was observed for rictor, a component of mTOR complex 2 (mTORC2) which provides substrate specificity for AKT 14. Protein kinase Cα (PKCα), which is phosphorylated by mTORC2 at serine 657,15, 16 was present and phosphorylated identically in resting platelets from all horses and throughout the time course after activation with α‐thrombin (Fig 4B).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Mammalian target of rapamycin (mTOR) phosphorylates AKT on S473, and was present at comparable levels in platelets from normal and affected horses at these time points. This also was observed for rictor, a component of mTOR complex 2 (mTORC2) which provides substrate specificity for AKT 14. Protein kinase Cα (PKCα), which is phosphorylated by mTORC2 at serine 657,15, 16 was present and phosphorylated identically in resting platelets from all horses and throughout the time course after activation with α‐thrombin (Fig 4B).…”
Section: Resultssupporting
confidence: 56%
“…Normal levels of the mTORC2 components rictor and mTOR, as well as normal phosphorylation of the mTORC2 target serine 657 of PKCα after activation, provide evidence that this complex functions normally in AET platelets 15, 16. Although recent studies have shown that pharmacological inhibition of mTORC2 does not inhibit aggregation of washed platelets, the role of this complex in fibrinogen binding and α‐granule secretion remains undefined 14, 24. Glycogen synthase kinase (GSK‐3β) phosphorylation also occurs normally after the pharmacological inhibition of mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…Ovaries ( n  = 3 for each genotype) were collected from 3‐ and 6‐month‐old Clpp +/+ and Clpp −/− mice and western analysis was performed to assess the expression of p‐S6 and p‐AKT473 proteins, as downstream mediators of mTORC1 and mTORC2 activation (Sarbassov, Guertin, Ali & Sabatini, 2005). There was no significant difference in p‐S6 or p‐AKT473 expression at 3 months between Clpp −/− and Clpp +/+ mice ovaries (Figure 6a–b), while both p‐S6 (1 ± 0.30 vs. 3.29 ± 0.56, p  <   0.01) and p‐AKT473 (1 ± 0.40 vs. 2.452 ± 0.57 p  <   0.05) protein expressions were significantly increased in Clpp −/− mice ovaries at 6 months (Figure 6c–d).…”
Section: Resultsmentioning
confidence: 99%
“…Both inhibitors blocked the phosphorylation of YAP in B cells infected with Salmonella WT (Figure 1(c,d). To strengthen the role of Akt in YAP phosphorylation during Salmonella infection of B cells, we generated a conditional knockout mouse for the Rictor gene, which is part of the mTORC2 complex responsible for phosphorylating Akt at serine 473 [38]. (Figure S3).…”
Section: Resultsmentioning
confidence: 99%